A Study of Hypoalbuminaemia in Chronic Liver Disease and its Correlation with Development of Esophageal Varices (Bangladesh Journal of Medicine, 2013)
Background: The aim and objective of this study was to evaluate relationship of serum albumin and esophageal varices in chronic liver disease (CLD) admitted in the medicine unit and gastroenterology department of Dhaka Medical College Hospital. Method: In this cross-sectional study, a total number of 100 randomly selected, clinically diagnosed patients of chronic liver disease were studied from June 2010 to November 2010 (6 months). All patients were assessed as per Child-Pugh class and had full blood count, HBsAg, Anti-HCV antibodies by ELISA, abdominal ultrasound and Endoscopy of upper gastrointestinal tract. Patients were divided into Group A (serum albumin